Bilateral agreement for the academic year 2007/2010 Socrates Programme: higher education Erasmus between - University of Tampere (Tampereen yliopisto) and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Socrates programme. - Erasmus subject area: International relations.